2008
DOI: 10.1016/j.neuron.2008.01.030
|View full text |Cite
|
Sign up to set email alerts
|

State-Dependent Bidirectional Modification of Somatic Inhibition in Neocortical Pyramidal Cells

Abstract: Cortical pyramidal neurons alter their responses to input signals depending on behavioral state. We investigated whether changes in somatic inhibition contribute to these alterations. In layer 5 pyramidal neurons of rat visual cortex, repetitive firing from a depolarized membrane potential, which typically occurs during arousal, produced long-lasting depression of somatic inhibition. In contrast, slow membrane oscillations with firing in the depolarized phase, which typically occurs during slow-wave sleep, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
96
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 59 publications
15
96
0
Order By: Relevance
“…Recent in vitro study reported state-dependent insertion of GABA A receptors in the pyramidal cells of the rat visual cortex (Kurotani et al, 2008). Thus, state-dependent insertion or modulation of GABA A receptors of the postsynaptic membrane (Gaiarsa et al, 2002;Jacob et al, 2008) of mitral cells might explain our results of state-dependent change of granule-tomitral inhibition.…”
supporting
confidence: 50%
“…Recent in vitro study reported state-dependent insertion of GABA A receptors in the pyramidal cells of the rat visual cortex (Kurotani et al, 2008). Thus, state-dependent insertion or modulation of GABA A receptors of the postsynaptic membrane (Gaiarsa et al, 2002;Jacob et al, 2008) of mitral cells might explain our results of state-dependent change of granule-tomitral inhibition.…”
supporting
confidence: 50%
“…Future studies will be needed to assess how MD and subsequent sleep affect postsynaptic currents in principal neurons. Enhancement of postsynaptic GABA receptor signaling has been reported in vitro in response to "sleep-like" patterns of activity (30), but it is unclear whether this finding translates to the natural sleep state or how this change in inhibition affects cortical circuit function.…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to a synapse-specific proportional reduction of synaptic weights of synchronously firing neurons (Birtoli and Ulrich, 2004;Czarnecki et al, 2007). NREM-sleep-related discharge patterns were also shown to enhance GABAergic synaptic transmission (Kurotani et al, 2008). Together, these processes may contribute to the overall decline in excitability observed during sleep with field potential recordings (Barnes et al, 1977;Vyazovskiy et al, 2008).…”
Section: Functional Implicationsmentioning
confidence: 99%